PENYUTRADARAAN FILM DRAMA KOMEDI “HANI” DENGAN PENDEKATAN KEARIFAN LOKAL - Muhammad Saleh; Cito Yasuki Rahmad (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2023)
The Indonesian nation and its people are known as a pluralistic society that has various tribes, ethnicities,cultures, religions, races, customs and languages. The community and the environment have local wisdom values that need to be considered, as a form of character and meaning in life. The concept of the directorial work of the comedy drama film “HANI” raises the background of the story about early marriage age, in the form of verbal and slapstick comedy dramas, with the local language style of the pendalungan community with a light demeanor. The comedy-drama film “Hani” was directed with the local culture of pendalungan to create a comedy-drama in the storyline, as well as local actors who provide and create comedy-drama elements into a complete audiovisual work with easy-to-understand and entertaining problems.